THE USE OF PERFORMANCE-BASED ASSESSMENT TOWARD EFL STUDENTS’ LEARNING ATTITUDE - Siti Amalia Rachmawati (Discovery, 2021)
Abstract: This study aims to identify the use of performance-based assessment toward the EFL students’ learning attitude of how it can be implemented for the EFL students and what are the impacts of using performance-based assessment toward the EFL students’ learning attitude. This paper identifies the EFL teachers’ opinions about the implementation and the impact of performance-based assessment for the EFL students. The data analysis of this study is based on the theory about performance-based assessment and students’ learning attitudes. The method used in this research is descriptive qualitative research method which deals with data that are in the form of words and not showed as numeric data by using interview data toward two EFL teachers in different level. This study results show that the English teachers have many ways in implementing performance-based assessment and this implementation brings positive and negative impacts. In clonclusion, each of English teacher has their own way to apply this kind assessment so that it can give the good effect to their students’ learning attitude. Keywords: Alternative Assessment, Performance-Based Assessment, EFL students’ learning Attitudes Abstrak: Penelitian ini bertujuan untuk mengidentifikasi penggunaan penilaian berbasis kinerja terhadap sikap belajar siswa EFL tentang bagaimana penerapannya untuk siswa bahasa Inggris dan apa dampak penggunaan penilaian berbasis kinerja terhadap sikap belajar siswa tersebut. Makalah ini mengidentifikasi pendapat guru bahasa Inggris tentang penerapan dan dampak penilaian berbasis kinerja untuk para siswanya. Analisis data penelitian ini didasarkan pada teori tentang penilaian berbasis kinerja dan sikap belajar siswa. Metode yang digunakan dalam penelitian ini adalah metode penelitian kualitatif deskriptif yang berhubungan dengan data yang berupa kata-kata dan tidak ditampilkan sebagai data numerik dengan menggunakan data wawancara kepada dua orang guru bahasa Inggris di jenjang yang berbeda. Hasil penelitian ini menunjukkan bahwa guru bahasa Inggris memiliki banyak cara dalam menerapkan penilaian berbasis kinerja dan penerapan ini membawa dampak positif dan negatif. Kesimpulannya, setiap guru bahasa Inggris memiliki cara masing-masing dalam menerapkan asesmen semacam ini sehingga dapat memberikan pengaruh yang baik terhadap sikap belajar siswanya. Kata kunci: Penilaian Alternatif, Penilaian Berbasis Kinerja, Sikap Belajar Siswa Bahasa Inggris